Impact resistance of cork-skinned marine PVC / GRP sandwich laminates. (November 2022) - Sutherland, L.S.; Guedes Sores, C.
Abstract: The introduction of a thin cork layer was investigated as a means to improve the impact resistance of composite foam sandwich laminates whilst maintaining structural performance. Six configurations of this 'cork-skinned' sandwich architecture were evaluated via extensive experimental comparisons with a 'baseline' GRP/ PVC foam sandwich laminate as typically used in marine structures. The concept improved perforation resistance (by up to 60%) for both quasi-static indentation and impact loading rates, albeit with an increase in laminate weight. However, initial (slight) damage resistance and bending strength can be compromised if the detailed laminate architecture is not designed with care. Highlights: A cork skin can increase the perforation resistance of sandwich laminates by 60%. Neither beam shear nor bending stiffness, nor shear strength were compromised. Thinner upper impacted faces had slightly reduced beam bending strengths. Laminate performance ranking varied with both damage criteria and loading case. Resistance to all damage types was higher for impact than for quasi-static loading.